Intraregional variability of exotic and native zooplankton in Basque coast estuaries (inner Bay of Biscay): effect of secondary dispersion, estuary features and regional environmental gradients. - Barroeta, Z., I. Uriarte, A. Iriarte & F. Villate (Hydrobiologia, 2023)
The zooplankton of five estuaries of the Basque coast (southeast Bay of Biscay) was surveyed in summer 2019 to check the intraregional spread of exotic species and analyse the cross-estuary differences in brackish and neritic communities related to the arrival of exotic species and the summertime geographic gradient of water temperature. Results revealed that all the studied estuaries have been colonized by Oithona davisae but not by Acartia tonsa and Pseudodiaptomus marinus. Environmental constraints due to estuarine hydrological features partly explained such differences, and the role of secondary spread opportunities remained less clear. Cross-estuary differences in the brackish community mainly reflected changes in the dominance of the native species Acartia bifilosa relative to different exotic copepod species. The neritic holoplankton differed in the contribution of thermophilic species in agreement with the thermal west-east increase of surface water temperature in the inner Bay of Biscay in summer. The detection of large numbers of larvae of the exotic crab Rhithropanopeus harrisii only in one of the estuaries highlighted the role of exotic benthic species in enhancing intraregional differences in estuarine meroplankton. Differences in the dominance of neritic or brackish species as a function of salinity and distance from coastline were also explored.